Educational research : planning, conducting, and evaluating quantitative and qualitative research - Creswell, John W. (Pearson Education Limited, 2021)
This title is a Pearson Global Edition. The Editorial team at Pearson has worked closely with educators around the world to include content which is especially relevant to students outside the United States. A practical, step-by-step core research text that balances coverage of qualitative, quantitative and combined methods Educational Research: Planning, Conducting, and Evaluating Quantitative and Qualitative Research offers a truly balanced, inclusive, and integrated overview of the processes involved in educational research. This text first examines the general steps in the research proce.